TEMUAN FITUR DAN DATA ORGANIK DI SITUS LIYANGAN SERTA TANTANGAN KONSERVASINYA - Sugeng Riyanto (Borobudur, 2022)
The Liyangan site in Purbosari Village, Ngadirejo District, Temanggung Regency, Central Java was discovered by sand miners in 2008 and has been studied by the Yogyakarta Archeology Center since 2009. The results of this study shows that the Liyangan site is an ancient settlement consisting of residential areas, agriculture, and areas of worship. Chronologically, the ancient Liyangan settlement began to grow at least in the 2nd century and developed gradually until the ancient Matarām kingdom, even up to the 11th century. The large-scale eruption of Mount Sindoro in the 11th century stopped that civilization. In addition to obliterating the ancient Liyangan settlement, the eruption material sealed the site and archaeological data so that some of it was naturally conserved. The data includes 1) structures and buildings, 2) features, 3) artifacts such as ceramic, pottery, stone, as well as artifacts made of metal, 4) organic data, and 5) ecofact. That is why the Liyangan site is a special site because it is supported by extraordinary archaeological data findings, especially features and organic materials. On the other hand, the presence of this data presents challenges related to its conservation as well as maintaining the uniqueness of the Liyangan site. This article was compiled to explain this through a desk study to obtain information related to the conservation of features and organics as an integral part of the extraordinary ancient Liyangan settlement.